KARAKTERISTIK PRODUK FERMENTASI DARI BAHAN BAKU KOMBINASI SUSU KAMBING DENGAN EKSTRAK KEDELAI, EKSTRAK JAGUNG, ATAU SANTAN KELAPA [Characterization of Fermented Products Made From Caprine Milk in Combination with Soy Extract, Corn Extract or Coconut Extra - Hartati Chairunnisa; Wendry Setiyadi Putranto; Stefanus Jemianus Lepa (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2010)
The aim of this study was to determine the best combination of caprine milk with soy extract, corn extract, or coconut extract in the production of flavored fermented milk products. Products were analyzed for the lactic acid content, crude protein, viscosity and also organoleptic properties (color, texsture, flavour, overall acceptance). This study was performed by a Completely Randomized Design with four kind of treatments, i.e.caprine, caprine milk in combination with soy extract, corn extract, or coconut extract with five replications. The result indicated that the caprine milk in combination with soy extract resulted an acceptable flavored fermented milk product containing 0.78% lactic acid, 6.62% crude protein, and had a viscosity of 2120 centipoise. The texture of the most liked flavoured fermented milk product was viscous to most viscous, and the flavour was slightly sour to sour.